Editorial - Sarojini Nadar (African Journal of Gender and Religion (AJGR))
What can we learn about the intersections of gender and religion from plays, films, medieval epics, poetry, and ancient biblical texts? A great deal, if the five articles in this issue of the journal are anything to go by. These articles offer in-depth analyses and profound insights about gen-dered relationships and the ways in which asymmetrical power is mani-fest in these various forms of media. Drawing on a range of inter-disciplinary methods, the articles in this issue invite us to consider how literature, film, poetry, and ancient texts act as a mirror for, and a window to religiously and culturally sanctioned gendered roles, behaviours, and attitudes.